The impact of media on surge capacity in emergency departments: a study on rabies vaccination uptake - Suleyman Alpar; Figen Unal Colak; Bulent Kaya; Sarper Yilmaz (BMC Emergency Medicine)
Abstract Objective This study aims to explore the influence of media coverage on rabies vaccination practices and emergency department (ED) visits in Turkey, a country characterized by a substantial volume of patient admissions to EDs. Additionally, the study examines the impact of media-driven public concern on ED surge capacity, highlighting the challenges emergency physicians face in managing sudden patient influxes. Methods This retrospective, descriptive, cross-sectional study was conducted at a single center. To assess the influence of media on vaccination practices in EDs and its effect on ED surge capacity, the Causal Impact package and interrupted time-series analysis using autoregressive integrated moving average (ARIMA) modeling were employed. Results A total of 27,293 rabies vaccinations were administered at the study center within one year, with distribution as follows: 37.3% for the first dose, 33.4% for the second dose, and 29.2% for the third dose. Following rabies-related news, there was an average increase in the daily number of administered doses. The applied model indicated variances of 41.8%, 39.4%, and 38.5% for the respective doses, corresponding to daily increases of 7.73, 10.25, and 9.07 vaccinations. In the absence of rabies news, the expected daily doses would have been approximately 29 ± 1.7, 27 ± 1.4, and 24 ± 1.4, respectively. Rabies-related news resulted in absolute effects of 11 ± 1.7, 9 ± 1.4, and 9 ± 1.4 vaccinations and relative effects of 38 ± 8%, 35 ± 7.3%, and 38 ± 8.5% for the first, second, and third doses, respectively. Conclusion The presence of a rabies-related news story, coupled with an increase in rabies-related Google searches, was associated with a significant rise in rabies vaccinations administered in EDs. Media coverage of attention-captivating events can contribute to increased ED visits. Media plays a significant role in influencing ED utilization. Clinical trial number Not applicable.